2020
DOI: 10.1177/1464419320943396
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and experimental analysis of axial force generated by a drive shaft system

Abstract: The drive shaft system with a tripod joint is known to cause lateral vibration in a vehicle due to the axial force generated by various contact pairs of the tripod joint. The magnitude of the generated axial force, however, is related to various operating factors of the drive shaft system in a complex manner. The generated axial force due to a drive shaft system with a tripod joint and a ball joint was experimentally characterized considering ranges of operational factors, namely, the input toque, the shaft ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Four force sensors for measuring the AFF are installed in the hydraulic actuator end. The measured results in Feng et al (2020) have shown that the test bench has a good repeatability of measurement of the AFF and the measurement accuracy of the test bench is high.…”
Section: Model Verificationmentioning
confidence: 96%
See 1 more Smart Citation
“…Four force sensors for measuring the AFF are installed in the hydraulic actuator end. The measured results in Feng et al (2020) have shown that the test bench has a good repeatability of measurement of the AFF and the measurement accuracy of the test bench is high.…”
Section: Model Verificationmentioning
confidence: 96%
“…A test bench (TS GIM GmbH, Germany) for measuring the AFF of drive-shaft systems is shown in Fig. 5, which has been discussed in detail in Feng et al (2020). In short, the ball joint and the tripod joint are connected to the control motor and the hydraulic actuator, respectively.…”
Section: Model Verificationmentioning
confidence: 99%
“…Substituting Eqs. (30), (31) and 33into Eq. (32), the comprehensive curvature coefficient Kh between the roller and the track can be obtained as follows:…”
Section: Comprehensive Curvature Coefficient Between the Roller And Tmentioning
confidence: 99%
“…According to the analysis in Section 3.5, the main factors influencing the NGAF include the fractal parameters (namely, the fractal dimension and the characteristic length scale), the material parameters (namely, the elastic modulus, the Poisson's ratio and the yield strength), the operating conditions (namely, the articulation angle and the shaft angular position) and the correction coefficient. Since the effects of the operating conditions on the NGAF have been analyzed in [18,31], this section only analyzes the effects of the fractal parameters, the material parameters and the correction coefficient on the NGAF. The initial analysis values of the input parameters of the NGAF fractal model (Eq.…”
Section: Effects Of Factors On the Ngafmentioning
confidence: 99%
See 1 more Smart Citation